Thinning of originally-existing, mature myelin represents a nondestructive form of myelin loss in the adult CNS - Lin, Min Li; Lin, Wensheng (Frontiers in Cellular Neuroscience, 2025)
The main function of oligodendrocytes is to assemble and maintain myelin that wraps and insulates axons in the central nervous system (CNS). Traditionally, myelin structure, particularly its thickness, was believed to remain remarkably stable in adulthood (including early and middle adulthood, but not late adulthood or aging). However, emerging evidence reveals that the thickness of originally-existing, mature myelin (OEM) can undergo dynamic changes in the adult CNS. This overview highlights recent findings on the alteration of OEM thickness in the adult CNS, explores the underlying mechanisms, and proposes that progressive thinning of OEM represents a novel, nondestructive form of myelin loss in myelin disorders of the CNS.